Analysis of Mandarin Language Course Needs for Students of the Economic Education Study Program - Afrimonika, Yoanna; Khairullah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
Mandarin is becoming one of the most essential foreign languages ​​to learn due to China's rapid and dominant economic and political advancements. This trend has led to the integration of Mandarin language instruction in both formal and non-formal education settings, including within the Economics Education Study Program at Tanjungpura University. To select teaching methods and materials that align with student needs, it is crucial to conduct a needs analysis of the Mandarin language courses for 46 students enrolled in the Economics Education Study Program at Tanjungpura University. This study employs a qualitative descriptive approach, collecting data through a questionnaire distributed via Google Forms. The findings indicate that the majority of students are beginner learners who require foundational learning strategies. These strategies should be reinforced with more interactive classroom activities, such as translation exercises, speaking practice, and group-based learning. The study emphasises the importance of providing materials and topics relevant to students' fields of study. It is anticipated that these findings will serve as a valuable reference for designing teaching methods and materials that are well-suited to the academic and professional needs of the students.